Comparison Analysis of Single Loop Resonator Based Miniaturized Triple-Band Planar Monopole Antennas - Kaimin Wu; Yongjun Huang; Ruiming Wen; Jian Li; Guangjun Wen (International Journal of Antennas and Propagation)
We systemically analyze and discuss a group of miniaturized triple-band planar monopole antennas by integrating with a single loop resonator (SLR) as part of the radiation patch. Two configurations (rectangular and circular shaped radiation patches) are presented and the corresponding SLRs are integrated in the patches to contribute additional operating frequencies. Two feed techniques (coplanar waveguide and microstrip feeds) are performed to couple the electromagnetic waves. The conventional planar monopole antennas without the SLRs are also analyzed comparatively. Numerical and experimental methods are performed to demonstrate and discuss the proposed designs.